The Influence of Finger Grip Relaxation on The Intensity of Perineal Wound Pain During Wound Treatment in Post Partum Mothers at Sundari Hospital - Lilis Pujiati; Suherni; Heni Triana (PT Inovasi Pratama Internasional, 2023)
The delivery process often causes injuries and trauma to the uterine and vaginal areas. Especially those who do vaginal delivery. This wound can cause uncomfortable feelings and also quite severe pain when giving birth to pregnant women. And in order to reduce or overcome this pain, of course there are several ways that can be done to help pregnant women who are in labor so that pain can be overcome during labor. The purpose of this study was to find out and also obtain information and data on how the effect of holding finger relaxation can overcome and become the management of perineal wound pain in postpartum mothers for respondents or informants who control and deliver the process at the Sundari General Hospital. This study used pre and post test systems based on control of groups of respondents or informants in Sundari Public Hospital. In this study, there were 50 postpartum mothers who experienced perineal injuries. From this population the experimental group consisted of 25 people, while the control group also consisted of 25 respondents. For sampling using a purposive sampling technique where the research instrument will use an observation sheet with the NRS pain scale or Numerical Ra Scale as the data to be collected. The data collection will be analyzed using the Mann-Whitney system. And the effect of finger grip relaxation on perineal wound pain in postpartum mothers carried out at Sundari General Hospital can be an application process for mothers who are about to give birth to reduce pain.